CONTRIBUIÇÃO PARA A RENOVAÇÃO DAS ABORDAGENS PEDAGÓGICAS NO PROCESSO DE FORMAÇÃO DE ENFERMEIROS - Cesar Cavalcanti da Silva; Ana Tereza Medeiros Cavalcanti da Silva; Casandra Genoveva R. M. Ponce de Leon; Maria Benegelânia Pinto (Universidade Federal do Paraná, 2004)
O artigo sugere a renovação das abordagens pedagógicas no processo de formação de enfermeiros e aponta a abordagem por Competências como concepção pedagógica capaz de compatibilizar os aspectos técnicos e políticos nos processos de formação profissional. Contribution for the renovation of the pedagogical approach during the nurses graduation process Abstract The article suggests the renovation of the pedagogical approaches in the nurses graduation process, and points the competency approach as a pedagogical conception capable to make compatible the technician and politicians aspects in the processes of professional formation.